Sweet Scents: Nectar Specialist Yeasts Enhance Nectar Attraction of a Generalist Aphid Parasitoid Without Affecting Survival - Sobhy, Islam S.; Baets, Dieter; Goelen, Tim; Herrera-Malaver, Beatriz; Bosmans, Lien; Van den Ende, Wim; Verstrepen, Kevin J.; Wäckers, Felix; Jacquemyn, Hans; Lievens, Bart (Frontiers in Plant Science, 2018)
Floral nectar is commonly inhabited by microorganisms, mostly yeasts and bacteria, which can have a strong impact on nectar chemistry and scent. Yet, little is known about the effects of nectar microbes on the behavior and survival of insects belonging to the third trophic level such as parasitoids. Here, we used five nectar-inhabiting yeast species to test the hypothesis that yeast species that almost solely occur in nectar, and therefore substantially rely on floral visitors for dispersal, produce volatile compounds that enhance insect attraction without compromising insect life history parameters, such as survival. Experiments were performed using two nectar specialist yeasts (Metschnikowia gruessii and M. reukaufii) and three generalist species (Aureobasidium pullulans, Hanseniaspora uvarum, and Sporobolomyces roseus). Saccharomyces cerevisiae was included as a reference yeast. We compared olfactory responses of the generalist aphid parasitoid Aphidius ervi (Haliday) (Hymenoptera: Braconidae) when exposed to these microorganisms inoculated in synthetic nectar. Nectar-inhabiting yeasts had a significant impact on nectar chemistry and produced distinct volatile blends, some of which were attractive, while others were neutral or repellent. Among the different yeast species tested, the nectar specialists M. gruessii and M. reukaufii were the only species that produced a highly attractive nectar to parasitoid females, which simultaneously had no adverse effects on longevity and survival of adults. By contrast, parasitoids that fed on nectars fermented with the reference strain, A. pullulans, H. uvarum or S. roseus showed shortest longevity and lowest survival. Additionally, nectars fermented by A. pullulans or S. roseus were consumed significantly less, suggesting a lack of important nutrients or undesirable changes in the nectar chemical profiles. Altogether our results indicate that nectar-inhabiting yeasts play an important, but so far largely overlooked, role in plant-insect interactions by modulating the chemical composition of nectar, and may have important ecological consequences for plant pollination and biological control of herbivorous insects.